2022
DOI: 10.1136/ard-2022-222824
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of major adverse cardiovascular and venous thromboembolism events in patients with rheumatoid arthritis exposed to JAK inhibitors versus adalimumab: a nationwide cohort study

Abstract: ObjectivesTo assess the risk of major adverse cardiovascular events (MACEs) and venous thromboembolism events (VTEs) among patients initiating a Janus kinase inhibitor (JAKi) (tofacitinib and baricitinib) versus adalimumab in a large real-world population of patients with rheumatoid arthritis.MethodsWe conducted a nationwide population-based cohort study of the French national health data system, the exposed group initiating a JAKi and non-exposed group initiating adalimumab. We included all individuals who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 28 publications
(49 reference statements)
5
44
1
1
Order By: Relevance
“…However, Salinas et al made no adjustment based on previous treatment failures or disease activity, nor carried out any analysis on patient subpopulations with or without relevant risk factors. As highlighted before, Hoisnard et al did not show differences for VTEs in patients treated with JAKi compared with those who received adalimumab using SNDS data, including in a subpopulation similar to the at-risk population of the baricitinib studies presented here (aged 65 years or older with at least one risk factor for cardiovascular disease) [ 44 ]. The occurrence of VTE in at-risk patients who received baricitinib treatment in the RA clinical programme is thus associated with previously identified independent VTE risk factors, such as previous VTE, older age, obesity, malignancy, and immobility [ 46 ].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, Salinas et al made no adjustment based on previous treatment failures or disease activity, nor carried out any analysis on patient subpopulations with or without relevant risk factors. As highlighted before, Hoisnard et al did not show differences for VTEs in patients treated with JAKi compared with those who received adalimumab using SNDS data, including in a subpopulation similar to the at-risk population of the baricitinib studies presented here (aged 65 years or older with at least one risk factor for cardiovascular disease) [ 44 ]. The occurrence of VTE in at-risk patients who received baricitinib treatment in the RA clinical programme is thus associated with previously identified independent VTE risk factors, such as previous VTE, older age, obesity, malignancy, and immobility [ 46 ].…”
Section: Discussionmentioning
confidence: 58%
“…Recently, Hoisnard et al, using data from SNDS after inverse propensity score treatment weighting, showed that there was no difference in risk of MACE (or VTE) between patients initiating a JAKi (60% baricitinib, 40% tofacitinib) and initiating the TNFi adalimumab. A subgroup analysis of patients aged 65 years or older, and with at least one risk factor for cardiovascular disease, also found no evidence of a difference in risk between the JAKi and adalimumab cohorts [ 44 ]. Further contextualization of these observational cohort studies with respect to ORAL Surveillance is hard to elucidate due to different study designs and endpoints (Cox model and time to event vs. incidence rates, as well as length of follow-up and methods of addressing confounding factors through propensity scores vs. inverse probabilities).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the risk of developing acute cardiovascular events, there is evidence showing that the risk for the occurrence of MACE is lower in patients treated with etanercept compared to TCZ [ 202 ] or tofacitinib (a janus kinase inhibitor) [ 203 ], while another study found no difference in the risk of MACE between patients treated with tofacitinib and with adalimumab [ 204 ].…”
Section: The Effects Of Biological Therapy On Cardiovascular Risk Fac...mentioning
confidence: 99%
“…[15] In addition, the real-world data of U.S.A and French showed non-significance between JAKi and TNFi in aspect of MACE risk (HR = 1.01 [95% CI 0.83 -1.23] for U.S.A, HR = 1.0 [95% CI 0.7 -1.6] for French). [13,14] The mortality rates associated with heart disease differ according to ethnicity, and are considerably lower in Asian or Pacific Islander populations than in other ethnic groups (e.g., Black, Caucasian, or Hispanic). [33] In the present study, the risk of CVD (including ACS, stroke, CV-related mortality, and MACE) was not increased in the JAKi group.…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%
“…[12] Two insurance claim data analysis of U.S.A and French showed that JAKi use did not increased risk of MACE nor VTE in real world data. [13,14] Furthermore, risk for MACE was increased only in RA patients with baseline atherosclerotic cardiovascular disease (ASCVD), but not in RA patients without ASCVD in post hoc analysis of ORAL surveillance study. [15] After ORAL surveillance, the U.S. FDA, European Medicines Agency (EMA), and Korean FDA limited use of all JAKis to patients with RA for whom JAKi treatment was the only option.…”
Section: Introductionmentioning
confidence: 99%